Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1039/d3fo00775h
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics alleviate cartilage degradation and inflammation in post-traumatic osteoarthritic mice by modulating the gut barrier and fecal metabolomics

Abstract: Osteoarthritis (OA) is a degenerative joint disease characterized by articular cartilage degeneration, subchondral bone sclerosis, synovial hyperplasia and as the main pathological manifestations. This study aims to investigate the protective...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 46 publications
0
1
0
Order By: Relevance
“…In vivo treatment of adrenic acid markedly prevented inflammation and alleviated the arthritis symptoms in an LTB4dependent murine arthritis model [18]. Another study demonstrated that intestinal metabolic disturbance occurred in a post-traumatic osteoarthritic (PTOA) mouse model with feces adrenic acid significantly decreased [19].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In vivo treatment of adrenic acid markedly prevented inflammation and alleviated the arthritis symptoms in an LTB4dependent murine arthritis model [18]. Another study demonstrated that intestinal metabolic disturbance occurred in a post-traumatic osteoarthritic (PTOA) mouse model with feces adrenic acid significantly decreased [19].…”
Section: Discussionmentioning
confidence: 97%
“…Prebiotic treatment could exert a beneficial influence on the joint degeneration of PTOA mice, possibly through compensating for such a decrease [19]. Furthermore, adrenic acid was found to be highly correlated with femur and tibia bone mineral density (BMD) [20].…”
Section: Discussionmentioning
confidence: 99%
“…In untargeted metabolomics experiments, an X500R HPLC-Q-TOF/MS (SCIEX) was used with an XSelect Premier HSS T3 column (100 mm × 2.1 mm, Waters Corporation, Milford, Massachusetts, USA) for chromatographic separation ( Jing et al, 2021 ). The mobile phase consisted of 0.1% formic acid in water (solvent A) and acetonitrile (solvent B), with a gradient duration of 18 min and a flow rate of 0.3 mL/min ( Mi et al, 2023 ). ESI was used for ionization in both positive and negative ion modes, with ion source gasses 1 and 2 set at 55 psi and curtain gas at 35 psi.…”
Section: Methodsmentioning
confidence: 99%